A Study on the Patterns of Drowning Cases Brought for Medico-legal Autopsy (Medico Legal Update, 2020)
Drowning is a form of death in which the atmospheric air is prevented from entering the lungs due to thesubmersion of the body in water or any other fluid medium1,2. Drowning can be classified as wet drowning(fresh or salt water), dry drowning, secondary drowning and the immersion syndrome or hydrocution (coldwater drowning).2,3,4,5 Drowning is an important public health issue with major impacts on human resourcewhich is a preventable phenomenon. According to National Crime Records Bureau, Ministry of HomeAffairs in 2014, in India, death due to drowning was 6.6%, making it third largest cause of death in India6India is a vast country having plenty of water bodies and an extensive coastline and under such conductivecircumstances, cause of death due to drowning is a frequent event where medico-legal experts are calledupon to investigate. With a view to investigate the epidemiological factors, a study was conducted in theDeptt. of Forensic Medicine, Gauhati Medical College for a period of 1 year. In our study we found that mostof the victims were males (82%) in the 31- 40 years age group (24.4%). Most of the victims had drownedin fresh water (94.5%) and running type (63.8%). A total of 34 cases constituting 26.77% had externalinjuries. Most of the cases were accidental in nature (78%). An exhaustive study to unearth these sociodemographicalfactors of drowning, hence should be conducted, to analyze their impact on population andits prevention.